203 Finding voices: young people's experiences of the emergency department. Issue 12 (23rd November 2020) - Keating, Liza; Wilson, Sarah; Hill, Jonathan; Dainty, Jack
Abstract : Aims/Objectives/Background: Self-harm among adolescents is a major concern both because it gives rise to considerable distress and disruption in young people's lives and it commonly recurs. There are currently wide variations in the care of this group of patients and it is widely reported that their experience in the emergency department is poor. Young people who have self-harmed may differ from others attending the ED and we need to know more about these differences to inform ED care and potential improvements. The aim of this study was to establish the needs and expectations among children and young people in the ED and to increase the understanding of the specific needs of adolescents who self-harm through comparison with another patient group in the ED. Methods/Design: We undertook a case-control study with adolescents attending for suspected fractures serving as the control group. Adolescents and their guardians were each given a questionnaire pack on arrival in ED, and again at least 2 hours later, thus capturing their expectations and pre-existing characteristics, and their experience. Trained research assistants were present in the ED seven days a week and covered 10 am till 10 pm. The study commenced in July 2019 and terminated early in March 2020 at the onset of the COVID 19 pandemic. Results/Conclusions: Young people who had self-harmed had significantly higher mean dissatisfaction scores than those with suspected fractures. They also had higher mean levels of emotional and interpersonal difficulties and these were associated with higher dissatisfaction scores. This is the first case-control study to show that dissatisfaction with the ED is at least partly a function of the particular mental health problems suffered by adolescents who self-harm. This in turn provides initial clues to the particular needs of this group of patients in whom the current management is widely reported as inadequate.